1999
DOI: 10.1111/j.1469-8749.1999.tb00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral evidence for working‐memory deficits in school‐aged children with histories of prematurity

Abstract: Cognitive performance in 7‐ to 9‐year‐old preterm neonatal intensive‐care survivors was compared with that in age‐matched control children. Non‐verbal memory span, spatial working‐memory abilities, planning, set‐shifting, and recognition memory for both spatial and patterned stimuli were assessed using the Cambridge Neuropsychological Testing Automated Battery. Relative to children in the control group, neonatal intensive‐care unit (NICU) survivors demonstrated 25% more memory errors on the spatial working‐mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 58 publications
6
51
2
1
Order By: Relevance
“…Considering that, to correctly perform this task, an infant has to hold in mind the information on the previous test, it was concluded that it is working memory that is adversely influenced by the premature birth. This conclusion is consistent with findings evidencing the impairment of spatial working memory in schoolchildren born prematurely [25]. The available data consistently testify to a partial deficit of working memory, i.e., the ability to use information kept in a short-term memory buffer, in EP infants.…”
Section: Discussionsupporting
confidence: 90%
“…Considering that, to correctly perform this task, an infant has to hold in mind the information on the previous test, it was concluded that it is working memory that is adversely influenced by the premature birth. This conclusion is consistent with findings evidencing the impairment of spatial working memory in schoolchildren born prematurely [25]. The available data consistently testify to a partial deficit of working memory, i.e., the ability to use information kept in a short-term memory buffer, in EP infants.…”
Section: Discussionsupporting
confidence: 90%
“…Although this cognitive function could be involved in the explanation of their performance, it is important to take into account that groups differed in the low difficulty condition, which requires keeping active only one position and probably did not demand high working memory resources. In relation to this, Luciana et al (1999) reported in 7-9-year-old preterm children that they did not differ from controls under low difficulty conditions (with searches for two or three items).…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies reported visuospatial memory alterations in preterm children (Clark & Woodward, 2010;Luciana, Lindeke, Georgieff, Mills, & Nelson, 1999;Omizzolo et al, 2013;Vicari, Caravale, Carlesimo, Casadei, & Allemand, 2004). Omizzolo et al (2013) showed that 7-year-old very preterm children were impaired in comparison to controls in different visuospatial tasks like block recall or dot locations.…”
Section: Discussionmentioning
confidence: 98%
“…Working memory involves holding relevant information in the mind for short times and is involved in completing increasingly complex tasks as children move through the school years. A study of working memory in LBW and VLBW children aged 7 to 9 years, who attended mainstream schools, and a control sample of full-term peers was conducted by Luciana et al (1999). Deficits in the areas of recognition memory, memory span, and spatial working memory were found in the LBW and VLBW children in comparison with their full-term peers.…”
Section: Executive Functionmentioning
confidence: 99%